(untitled) (IAHS Medical Journal, 2025)
Background: Monopolar Transurethral Resection of Prostate (TURP) is the conventional technique for enlarge prostate. In recent years, bipolar TURP has been increasingly being used by the urologist instead of conventional monopolar TURP. This study was aimed to compare the clinical efficacy and safety profile between monopolar TURP and bipolar Transurethral Resection In Saline (TURIS) system for the treatment of symptomatic Benign Enlargement of Prostate (BEP). Materials and methods: This Quasi Experimental Study was conducted in the Department of Urology, Chattogram Medical College Hospital over 110 consecutive patients from 2nd March 2021 to 1st March 2022. Patients were randomly divided in two groups: Monopolar group and bipolar group. Resection time, Bladder irrigation time, six hours postoperative change in Hemoglobin and Serum Sodium and change in International Prostate Symptom Score (IPSS) Quality of life (QoL) and Maximum flow rate (Qmax) after six weeks of surgery were compared in between two groups. Results: Out of 110 enrolled patients, 100 were available in the final follow-up (50 in each group) and included in the final analysis. Both the groups were similar at baseline in terms of their demographic, clinical and laboratory parameters. Duration of prostate resection in bipolar group was longer (68.28±10.62 versus 55.80±6.36 minutes, p<0.001) than the monopolar group. The mean drop in postoperative hemoglobin and serum sodium concentration were significantly lower in monopolar group than the bipolar group. No TUR syndrome occurred in the study patients. Blood transfusions were required in 2% and 16% of the cases respectively in the bipolar and monopolar group (p=0.031). Post operative Hospital stay was significantly shorter in bipolar group (2.08±0.74 versus 3.08±0.39 days) than the monopolar group. Both groups had significantly improved IPSS values, QoL values and maximum urinary flow rate values after six weeks reflected significantly higher improvement in the bipolar group compared to monopolar group. Conclusions: Bipolar TURP seems to be a promising alternative for the treatment of patients with BEP, with better efficacy and shorter hospital stay with conventional monopolar TURP, with less perioperative bleeding, serum sodium reduction and requirement of postoperative blood transfusion. IAHS Medical Journal Vol 7(2), December 2024; 30-35